EFFECT OF PRE- DRYING AND FRYING KINETICS OF SWEET POTATO (IPOMOEA BATATAS L.) CHIPS - JAGAMOHAN MEHER; BRAJA KISHORI MISHRA; PRAKASH NAYAK; VISHAL SINGH (The Bioscan, 2015)
Experiments were conducted at different drying temperature (40, 60 and 800C) and frying time (60, 120, 180, 240 and 300 Second). MINITAB statistical software was used to study the statistical analysis of independent and dependent variables in terms of ANOVA. Page’s model is showing best model with high coefficient of regression (r2) 0.9980, 0.9994 and 0.9980 than Exponential models, (r2) 0.9948, 0.9988 and 0.9950 for 20 mm thick slice at a temperature 40, 60 and 80ºC respectively. Oil content of 20 and 30 mm thick sweet potato chips were reported, 68.1 and 68.7% for fresh sample and after drying up to 5% moisture (db), oil content reduced up to 11.4 and 13.2 % respectively. Optimum quality of Sweet potato chips (Moisture content 1.25 % db, 39.1 % oil content and hardness 5.02 N) were obtained at fried temperature of 170ºC for 180 seconds and the sensory ratings were observed as Ra =5.8, Rh = 6.4, Rm = 6.1, Ro = 6.8. For colour of fried chips, moisture content and drying time have significant effect (p<0.05) and Pre-drying temperature was non-significant (p>0.05) for hardness of chips. The chips dried to lower moisture content had more hardness. Based on sensory rating chips dried at 200% db at a temperature of 60ºC and fried at 170ºC for 180 s resulted best quality of chips.